Pengembangan Media Big Book Untuk Pembelajaran Bahasa Indonesia di Kelas 3 Sekolah Dasar - Anggraini, Amelia; Kurniaman, Otang; Munjiatun, Munjiatun (Unversitas Katolik Santo Thomas, 2021)
This study aims to develop big book media for learning Indonesian in grade 3 elementary school and to determine the feasibility of big book learning media. This research uses research and development (R&D) methods using the FOUR-D (Define, Design, Develop and Disseminte) model. The data collection technique used is by using questionnaires and trials. The feasibility of big book learning media is obtained from the results of media validation and testing. Validation was carried out by material experts and learning media experts. The results of the research show that the validation of the material experts and the validation of the learning media experts are very valid. The trials used in this study were limited to 10 students and received a very good response. The results of this development research indicate that the big book media for learning Indonesian in grade 3 Elementary School is very suitable for use in learning in Elementary School.Â